2022
DOI: 10.1136/heartjnl-2021-320513
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of amiodarone or lidocaine versus placebo for out-of-hospital cardiac arrest

Abstract: ObjectiveClinical trials for patients with shock-refractory out-of-hospital cardiac arrest (OHCA), including the Amiodarone, Lidocaine or Placebo (ALPS) trial, have been unable to demonstrate definitive benefit after treatment with antiarrhythmic drugs. A Bayesian approach, combining the available evidence, may yield additional insights.MethodsWe conducted a reanalysis of the ALPS trial comparing treatment with amiodarone or lidocaine with placebo in patients with OHCA following shock-refractory ventricular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In a recent reanalysis of the ROC ALPS data using a Bayesian framework, treatment with amiodarone had higher probabilities of improved survival and neurologic outcome while treatment with lidocaine had a smaller probability of benefit (20). This aligns with our results, which suggest that lidocaine is not more effective than placebo if given very early after cardiac arrest but its potential relative benefit may increase progressively with increased time intervals to drug.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent reanalysis of the ROC ALPS data using a Bayesian framework, treatment with amiodarone had higher probabilities of improved survival and neurologic outcome while treatment with lidocaine had a smaller probability of benefit (20). This aligns with our results, which suggest that lidocaine is not more effective than placebo if given very early after cardiac arrest but its potential relative benefit may increase progressively with increased time intervals to drug.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one strategy might use the algorithm to provide earlier or higher-dose antiarrhythmic treatment or a lower or delayed dose of a vasopressor such as epinephrine (given its potential proarrhythmic effects) for those at high risk of refractory VF. [8][9][10][11][12][13][14][15] The algorithm might also be used to inform which patients could be considered for modified shock delivery strategies (vector change or double sequential defibrillation) or early transport for advanced hospital care such as an emergent coronary artery intervention or extracorporeal CPR. [16][17][18][19][20][21]…”
Section: Clinical Implications Of Algorithm Performancementioning
confidence: 99%
“…[5][6][7] Hence, the ability to predict refractory VF in advance of repeated shock failure could enable preemptive interventions targeted at improving the relatively poor outcomes of the refractory VF subgroup. Such therapies might include earlier or increased antiarrhythmic dose administration, [8][9][10][11][12] reconsideration of epinephrine use or dosage, [13][14][15] changes in how shocks are administered, 16 or expedited invasive interventions. [17][18][19][20][21] By contrast, empiric treatment of all patients with VF OHCA using such strategies may unnecessarily expose patients who achieve best outcomes under the current protocol, introducing potential risk among those unlikely to benefit.…”
mentioning
confidence: 99%
“…Time to drug administration is hard to quantify in unwitnessed arrests, and prompt drug administration is difficult in CA trials, with a mean time to medication administration of approximately 19 minutes after emergency medical services activation [ 7 ]. A more recent study utilized a Bayesian approach to reanalyze the ALPS data and suggested a 2.9% overall survival benefit for amiodarone (interquartile range (IQR) 1.4–3.8%) and 1.7% for lidocaine (IQR 0.8–3.2%) as compared to placebo [ 98 ]. This study also showed that amiodarone offered a strong probability (96%–99%) to improve neurological outcomes in refractory VT/VF patients, higher than for lidocaine or placebo (96%) [ 98 ] and as such amiodarone should be strongly considered till further data emerge for clinical use.…”
Section: Antiarrhythmicsmentioning
confidence: 99%